The choice of investment portfolios under uncertainty based on metal-ods and of models of fuzzy linear programming in the tensor basis - Мінаєва, Ю. І. (Problems of Informatization and Management, 2010)
The problems of solving fuzzy linear programming representation by-resistivity parameters of fuzzy model tensors of rank 2. The possibility of communication solution of this class of problems at the level of the set clear tasks of linear programming created for the 1-th invariants and tensor norms, modeling fuzzy pa-spectra